(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the existence of intercultural differences in the interpretation of human emotions, which in turn is reflected in the language system, the non-verbal expression of feelings such as the verbal expression is chosen differently in different linguistic cultures, in general, the linguistic-cultural specificity of the means of expressing non-verbal emotions is analyzed. Data were placed in the analysis using comparative-analytical methods. A detailed analysis of non-verbal means of emotional expression by linguocultural and psycholinguistics will reduce the difficulties in the communication process.